2020
DOI: 10.15537/smj.2020.11.25495
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and in-hospital mortality of COVID-19 adult patients in Saudi Arabia

Abstract: Objectives: To provide a detailed study of demographic, baseline comorbidities, clinical features, and outcome for Coronavirus disease 2019 (COVID-19) patients. Methods: A record-based case-series study conducted from March 23 to June 15, 2020 in King Saud Medical City, Riyadh, Saudi Arabia. Demographic data, clinical presentation, laboratory investigations, complications, and in-hospital outcome of COVID-19 patients collected with analysis of the clinical characteristi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
34
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 36 publications
3
34
1
Order By: Relevance
“…At King Abdullah Hospital in Bisha Province, Saudi Arabia, another retrospective study was done from March 20 to June 30, 2020, where 37 (27 %) of the 137 patients revealed diabetes [ 35 ]. In King Saud Medical City, Riyadh, Saudi Arabia, 768 COVID-19 patients were used in a record-based, case-series study, from March 23, 2020, to June 15, 2020, where 96.3 % were identified with the presence of more than one comorbidity of which the most frequent was diabetes mellitus (46.4 %) [ 36 ]. Another study from King Saud Medical City, Riyadh, Saudi Arabia, conducted from March 1, 2020, to June 30, 2020, found diabetes to be the most frequent (37.3 %) comorbidities among COVID-19 patients [ 37 ].…”
Section: Why Diabetes Is Important?mentioning
confidence: 99%
“…At King Abdullah Hospital in Bisha Province, Saudi Arabia, another retrospective study was done from March 20 to June 30, 2020, where 37 (27 %) of the 137 patients revealed diabetes [ 35 ]. In King Saud Medical City, Riyadh, Saudi Arabia, 768 COVID-19 patients were used in a record-based, case-series study, from March 23, 2020, to June 15, 2020, where 96.3 % were identified with the presence of more than one comorbidity of which the most frequent was diabetes mellitus (46.4 %) [ 36 ]. Another study from King Saud Medical City, Riyadh, Saudi Arabia, conducted from March 1, 2020, to June 30, 2020, found diabetes to be the most frequent (37.3 %) comorbidities among COVID-19 patients [ 37 ].…”
Section: Why Diabetes Is Important?mentioning
confidence: 99%
“… 1 Symptoms range from mild to severe pathological manifestations of the disease in the infected population with comorbidities, which are often linked to acute respiratory distress syndrome. 2 , 3 The 21st century has seen three new coronaviruses evolve to pose a global challenge to public health. The newly identified SARS‐CoV-2 shares similarities with the previously identified severe acute respiratory syndrome coronavirus (SARS) and Middle East respiratory syndrome (MERS), such as animal reservoirs, unpredictable emergence, rapid spread and serious infectious outcomes in humans.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple systems, including the respiratory, cardiovascular, neurological, musculoskeletal, and gastrointestinal systems, may be affected. The condition may rapidly deteriorate to acute respiratory distress syndrome (ARDS) in high-risk patients such as elderly and those with other medical comorbidities, such as heart, lung, kidney, or liver disorders [ 4 ].…”
Section: Introductionmentioning
confidence: 99%